Antimicrobial susceptibility profile of Acinetobacter species isolated from blood cultures in two Japanese university hospitals. (February 2014) - Kishii, Kozue; Kikuchi, Ken; Yoshida, Atsushi; Okuzumi, Katsuko; Uetera, Yushi; Yasuhara, Hiroshi; Moriya, Kyoji
ABSTRACT Carbapenem‐resistant Acinetobacter baumannii has rapidly spread worldwide. This study investigated antibiotic susceptibility and genotypic resistance of 123 consecutive blood culture isolates of Acinetobacter species collected between 2003 and 2011 in two Japanese hospitals. The isolates were assigned to 13 species. Carbapenem resistance was detected in four isolates. Only one A. baumannii isolate had blaOXA‐23 together with ISAba1; the remaining three isolates had IMP‐1 metallo‐β‐lactamase. Quinolone resistance was detected in five isolates that had point mutations in the quinolone resistance‐determining region. The predominance of various non‐A. baumannii species and low prevalence of carbapenem resistance among blood culture isolates of Acinetobacter species in two Japanese hospitals were confirmed.